The Role of the Political Participation of Informal Forces in Promoting Democracy and Shaping Public Policies - Mohiesn, Zainab Karim (Indonesian Journal of Public Policy Review, 2026)
General Background This study examines the expanding influence of informal political actors—political parties, media institutions, and civil society organizations—as a result of democratic transitions that have reshaped governance structures in Iraq. Specific Background Although constitutional guarantees endorse political participation, practical engagement remains constrained by historical authoritarianism, sectarian divisions, and weak institutional cultures. Knowledge Gap Existing research has not sufficiently explained how informal forces simultaneously foster democratic practices and shape public policy within Iraq’s evolving political landscape. Aims This study aims to analyze the mechanisms through which informal actors contribute to democratic consolidation and influence policymaking processes. Results Findings indicate that political parties dominate policy formation, media act as pressure mechanisms that expose corruption and shape public opinion, and civil society organizations enhance political awareness and citizen engagement despite structural limitations. Novelty The study provides a comprehensive, system-based analysis of informal forces’ roles in both advancing democratic transformation and directing policy outcomes in a post-conflict political system. Implications Strengthening legal frameworks, enhancing media independence, and empowering civil society are essential to ensuring inclusive policymaking, improving accountability, and supporting Iraq’s long-term democratic development.Highlight : Highlights how informal forces contribute to democratic development and policy formation. Underscores the influence of political parties, media, and civil society in shaping public decisions. Emphasizes that their impact varies according to the political system and democratic context. Keywords : Political Participation, Informal Forces, Democracy, Public Policies, Iraq